Output feedback full-order sliding mode control for a three-tank system. (February 2023) - Hosokawa, Akihiko; Mitsuhashi, Yusei; Satoh, Kazuki; Yang, Zi-Jiang
Abstract: A robust output feedback nonlinear control method is proposed for output tracking of an uncertain three-tank system by using only the level sensor of the target tank. By using a coordinate transformation, we first transform the system model into a canonical form with uncertainties. The canonical system's state variables are estimated by a higher-order sliding mode differentiator based on the measurement of the target tank's liquid level. Then based on the estimated state variables, a continuous full-order sliding mode controller is constructed which can eliminate the effects of both the additive and multiplicative uncertainties. Rigorous analysis is carried out to clarify the control performance. And the effectiveness of the proposed method is verified by experimental studies on the Inteco Multi-tank system. Highlights: A control method is proposed for output tracking of an uncertain three-tank system by using only the single level sensor of the target tank. We first transform the system model into a canonical form whose states are estimated by a higher-order sliding mode differentiator. A continuous full-order sliding mode controller is constructed and theoretical analysis is performed. The method is verified by experiments.